Answer:
The Answer is: y = -2/3x + 10/3
Explanation:
Given points (-1, 4) and (8, -2) first find the slope:
m = (y - y1)/(x - x1)
m = (4 - (-2)) / (-1 - 8)
m = 4 + 2 / -9
m = -6/9 = -2/3
Use the point slope form and point (8, -2) and slove for y:
y - y1 = m(x - x1)
y - (-2) = -2/3(x - 8)
y + 2 = -2/3x + 16/3
y = -2/3x + 16/3 - 2
y = -2/3x + 16/3 - 6/3
y = -2/3x + 10/3
Proof using the point (-1, 4):
f(-1) = -2/3(-1) + 10/3
= 2/3 + 10/3
= 12/3 = 4, giving point (-1, 4)
Hope this helps! Have an Awesome Day!! :-)